Treatment Challenge in COVID-19 Patients with Acute Kidney Injury in Hospital - Mirza Zaka Pratama; Achmad Rifa'i; Duma Sianturi (Universitas Brawijaya, 2022)
Renal, the main characteristic of COVID-19 infection. Acute kidney injury (AKI) has been documented in 20-50% of the hospitalized COVID-19 patients. Renal involvement among COVID-19 patients might be multifactorial. COVID-19 Patients with AKI significantly had higher mortality than patients without AKI. This case series reported severe COVID-19 with respiratory failure and AKI during admission to the hospital. All patients were admitted to the intensive care unit (ICU) and obtained the standard therapeutic protocols according to the COVID-19 severities. The first patient developed AKI in the three days of admission, while the second and third patients had AKI from the first day of admission. The patients had similar complications, including type 1 or 2 respiratory failures, secondary infection with sepsis, hyperpotassemia, and metabolic acidosis. The first and second patients underwent hemodialysis as indicated on these patients. However, the evaluation of their renal functions did not improve after that. The third patient did not receive the hemodialysis therapy and only obtained supportive treatment with adequate fluid therapy. The third patient was getting better on the 16th day of admission. In addition, the renal function test was getting normal after the 16th day of admission. The patient was discharged on the 19th day of admission in stable condition. Early recognition of renal involvement in COVID-19 infection, preventive measures, renal function monitoring, and therapeutic intervention were essential to reduce the morbidity and mortality of COVID-19 patients. Hospitalized patients should be monitored closely for their renal function to prevent renal function deterioration in the future.